Avaliação dos processos de lixiviação e biolixiviação para a recuperação de cobalto e lítio de baterias de íons de lítio - Menêzes, Luis Henrique dos Reis (2018)
The high growth in the consumption of mobile phones has resulted in the increase of electronic waste, such as lithium ion batteries (LIBs), which cause environmental damages, due to the release of heavy metals. The search for new sustainable methods to minimize this impact has been an alternative to the shortage of added-value commercial metals, such as Cobalt and Lithium. Therefore, this study aimed to evaluate the recovery of Co and Li in LIBs. In a first step, it was the leaching method, in which the potential of different organic acids (lactic, acetic, propionic, butyric and citric) as leachate was studied. These organic acids were used pure (3.4 M) or in mixture with sulfuric acid (sulfuric: organic / 1.25 M: 0.75 M), using milk whey permeate as reducing agent. Besides, the production of leachate from the fermentation of microbial consortium in order to obtain high concentration of organic acids was also evaluated. In the sequence this medium was applied in the leaching of the metals in association with sulfuric acid. From these tests, lactic acid in association with H2SO4 recovered 94.35% for Li and 90.90% for Co, whereas Co and Li recovery were less than 82% and 68% respectively, employing the other organic acids in association with sulfuric acid. Regarding to the use of pure organic acids, again, the lactic acid presented the best results, with recoveries around 57% Co and 64% lithium, while, the recoveries using other organic acids, varied between 0.27% and 53%. In the fermentation to obtain a medium with potential for leaching, the maintenance of the pH at 5.5 with repeated batch of milk whey permeate, allowed to achieve a leaching medium rich in organic acids that, combined with H2SO4, resulted in a 100% recovery for Co and 99.87% for Li. In a second step, bioleaching experiments with different microorganisms (anaerobic microbial consortium, A. ferrooxidans and A. thiooxidans, and P. oxalicum) were carried out, including the steps for defining the initial conditions of solid / liquid ratio, type and concentration of carbon source and initial pH. In the bioleaching assays, the acidophilic bacteria stood out both in terms of recovery (99% Li and 65% Co) and in process time. Nevertheless, considerable results were obtained with the application of the anaerobic microbial consortium, with recovery of 61.8% and 51.2%, respectively, for Li and Co, in 31 days. This result shows that the consortium is promising, since the operating conditions are moderate and easily adaptable in various environments.